Effects of Point Defects Introduced by Co-doping and Proton Irradiation in CaKFe4As4. (July 2020) - Kobayashi, Y; Pyon, S; Takahashi, A; Tamegai, T
Abstract: Introduction of point defects into superconductors through proton irradiation enhances their critical current density ( J c ). Similarly, chemical doping can also produce point defects, leading to the enhancement of J c . Iron-based superconductors (IBSs) have been investigated as promising materials for practical applications because of their large J c at high magnetic fields and temperatures. Recently, another promising IBS CaKFe4 As4 (1144-type) was found, and attracts much interest due to its characteristic feature such as stoichiometric superconductivity and the presence of novel planar defects. We have grown single crystals of Co-doped CaKFe4 As4 and clarified the effect of chemically-introduced point defects on J c . We also introduced point defects through 3 MeV proton irradiation, and compared the effect of point defects to J c .